Community Engagement in Cutaneous Leishmaniasis Research in Brazil, Ethiopia, and Sri Lanka: A Decolonial Approach for Global Health - Polidano, Kay; Parton, Linda; Agampodi, Suneth B.; Agampodi, Thilini C.; Haileselassie, Binega H.; Lalani, Jayasundara M. G.; Mota, Clarice; Price, Helen P.; Rodrigues, Steffane; Tafere, Getachew R.; Trad, Leny A. B.; Zerihun, Zenawi; et al. (Frontiers in Public Health, 2022)
Cutaneous leishmaniasis (CL) is a parasitic skin disease endemic in at least 88 countries where it presents an urgent, albeit often “neglected” public health problem. In this paper, we discuss our model of decolonial community engagement in the ECLIPSE global health research program, which aims to improve physical and mental health outcomes for people with CL. The ECLIPSE program has four interlinked phases and underpinning each of these phases is sustained and robust community engagement and involvement that guides and informs all activities in ECLIPSE. Our decolonial approach implies that the model for community engagement will be different in Brazil, Ethiopia and Sri Lanka. Indeed, we adopt a critical anthropological approach to engaging with community members and it is precisely this approach we evaluate in this paper. The data and material we draw on were collected through qualitative research methods during community engagement activities. We established 13 Community Advisory Groups (CAGs): in Brazil (n = 4), Ethiopia (n = 6), and Sri Lanka (n = 3). We identified four overarching themes during a thematic analysis of the data set: (1) Establishing community advisory groups, (2) CAG membership and community representation, (3) Culturally appropriate and context-bespoke engagement, and (4) Relationships between researchers and community members. During our first period of ECLIPSE community engagement, we have debunked myths (for instance about communities being “disempowered”), critiqued our own practices (changing approaches in bringing together CAG members) and celebrated successes (notably fruitful online engagement during a challenging COVID-19 pandemic context). Our evaluation revealed a gap between the exemplary community engagement frameworks available in the literature and the messy, everyday reality of working in communities. In the ECLIPSE program, we have translated ideal(istic) principles espoused by such community engagement guidance into the practical realities of “doing engagement” in low-resourced communities. Our community engagement was underpinned by such ideal principles, but adapted to local sociocultural contexts, working within certain funding and regulatory constraints imposed on researchers. We conclude with a set of lessons learned and recommendations for the conduct of decolonial community engagement in global health research.